2019
DOI: 10.1039/c8an02143k
|View full text |Cite
|
Sign up to set email alerts
|

An LC-MS profiling method reveals a route for apocarotene glycosylation and shows its induction by high light stress in Arabidopsis

Abstract: Apocarotenoid glycosylation serves as a valve regulating carotenoid homeostasis in plants and may contribute to their response to photo-oxidative stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 53 publications
0
21
0
Order By: Relevance
“…The presence of β‐CC can induce the xenobiotic detoxification pathway (D'Alessandro et al ., ), but the question arises as to whether it is also a substrate for these detoxifying chemical modifications. A possible answer to this question can be inferred from the recent demonstration that apocarotenoid hydroxylation and glycosylation are enhanced under high light conditions (Mi et al ., ). In this context, it is interesting to note that 1 O 2 as well as β‐CC have a strong up‐regulating effect on the expression of several glycosyl transferases in Arabidopsis leaves (Ramel et al ., , ).…”
Section: Homeostasis Of β‐Ccmentioning
confidence: 97%
See 1 more Smart Citation
“…The presence of β‐CC can induce the xenobiotic detoxification pathway (D'Alessandro et al ., ), but the question arises as to whether it is also a substrate for these detoxifying chemical modifications. A possible answer to this question can be inferred from the recent demonstration that apocarotenoid hydroxylation and glycosylation are enhanced under high light conditions (Mi et al ., ). In this context, it is interesting to note that 1 O 2 as well as β‐CC have a strong up‐regulating effect on the expression of several glycosyl transferases in Arabidopsis leaves (Ramel et al ., , ).…”
Section: Homeostasis Of β‐Ccmentioning
confidence: 97%
“…Although the measured levels of GAPO7 are just a fraction of the β‐CC concentration (1.67%), while most of the β‐ionone is present as GAPO9 (575%), this process suggests that β‐carotene derivatives are targeted by detoxifying mechanisms. Furthermore, unlike hydroxylated β‐ionone, hydroxy‐β‐cyclocitral was not detectable, suggesting a fast conversion to the glycosylated form and therefore the importance of this process in β‐CC homeostasis and in the regulation of β‐CC signaling (Mi et al ., ). The β‐CC metabolization described above limits its signaling role and may constitute a negative feedback mechanism to return 1 O 2 signaling back to unstressed levels.…”
Section: Homeostasis Of β‐Ccmentioning
confidence: 97%
“…The transcriptome reprograming process, triggered by β-cyclocitral, increases the plant tolerance to photo-oxidative stress and initiates acclimation to high light conditions (Ramel et al, 2012b). Recently, it was shown that high light leads to a significant increase in the content of glycosylated β-cyclocitral (Mi et al, 2019b), which might be a mechanism for deactivation of this signaling molecule (D’Alessandro and Havaux, 2019).…”
Section: Novel Carotenoid-derived Signaling Moleculesmentioning
confidence: 99%
“…The diapocarotenoid anchorene (C 10 ) is found in several plant species (e.g., tomato, carrot, spinach). Although it seems possible that the cleavage of C11–C12 and C11′–C12′ double bonds from carotenoids downstream of ζ‐carotene results in the production of anchorene, it is still unclear how it is formed (Jia et al ., 2019; Mi et al ., 2019). Anchorene was shown to promote the development of ANR (Figure 7b, left panel) (Jia et al ., 2019).…”
Section: Cyclic and Acyclic Apocarotenoids With Signaling Propertiesmentioning
confidence: 99%